Analysis of injury incidences in male professional adult and elite youth soccer players: A systematic review - Pfirrmann, D.; Herbst, M.; Ingelfinger, P.; Simon, P.; Tug, S. (Journal of Athletic Training, 2016)
Context: The incidence of injury for elite youth and professional adult soccer players is an important concern, but the risk factors for these groups are different.